2003
DOI: 10.1002/neu.10296
|View full text |Cite
|
Sign up to set email alerts
|

CREB in the pond snail Lymnaea stagnalis: Cloning, gene expression, and function in identifiable neurons of the central nervous system

Abstract: The pond snail Lymnaea stagnalis is an excellent model system in which to study the neuronal and molecular substrates of associative learning and its consolidation into long-term memory. Until now, the presence of cyclic AMP (cAMP)-responsive element binding protein (CREB), which is believed to be a necessary component in the process of a learned behavior that is consolidated into long-term memory, has only been assumed in Lymnaea neurons. We therefore cloned and analyzed the cDNA sequences of homologues of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
89
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 61 publications
(69 reference statements)
12
89
0
Order By: Relevance
“…In this regard, Jung et al (2010) showed that quercetin impaired memory formation in mice by affecting a transcription factor, CREB, that has been shown to play a key role in LTM formation across species (Costa-Mattioli et al, 2009). We know that CREB activation is necessary for LTM formation in Lymnaea (Sadamoto et al, 2004). We can conclude that quercetin prevents the enhancing effect of the heat stressor on LTM formation.…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, Jung et al (2010) showed that quercetin impaired memory formation in mice by affecting a transcription factor, CREB, that has been shown to play a key role in LTM formation across species (Costa-Mattioli et al, 2009). We know that CREB activation is necessary for LTM formation in Lymnaea (Sadamoto et al, 2004). We can conclude that quercetin prevents the enhancing effect of the heat stressor on LTM formation.…”
Section: Discussionmentioning
confidence: 92%
“…However, because the use of the typical protein synthesis inhibitors is not feasible for the ethical treatment of humans, researchers examined other possible pharmacological agents. One such agent was the beta-blocker propranolol, as it is probable that the adrenergic system is involved in at least certain aspects of the stressful event and also because propranolol may inhibit noradrenergicstimulated CREB phosphorylation, a necessary pathway involved in memory consolidation (Thonberg et al, 2002;Sadamoto et al, 2003;Azami et al, 2006). Systemic administration of propranolol in conjunction with memory reactivation disrupts reconsolidation of LTM in auditory and contextual fear and avoidance in rodents (Abrari et al, 2008;Debiec and Ledoux, 2004;Debiec et al, 2011;Przybyslawski et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Lymnaea CREB1 and CREB2 mRNAs and salmon GTH α2 RNA The nucleotide sequences of Lymnaea CREB1 and CREB2 mRNAs (accession numbers: AB041522 and AB083656, respectively; for details, see Sadamoto et al, 2004b) were used to design the primers and probes for qRT-PCR. We used the Primer Express software (version 1.0; PE Applied Biosystems) to design appropriate primers and fluorogenic probes for qRT-PCR assays.…”
Section: Preparation Of Primers Probes and Standard Curves Formentioning
confidence: 99%